THE EFFECT OF CURRENT RATIO, RETURN ON EQUITY, DEBT TO ASSET RATIO, INVENTORY TURNOVER, AND SALES GROWTH ON RETURN ON INVESTMENT IN RETAIL COMPANIESLISTED ON THE INDONESIAN STOCK EXCHANGE FOR THE PERIOD 2019–2024 - William Fransisco Wijaya; Jerico Thomas; Ike Rukmana Sari; Fauziah Kumalasari (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to analyze the impact of the Current Ratio (CR), Return on Equity (ROE), Debt to Asset Ratio (DAR), Inventory Turnover (IT), and Sales Growth (SG) on Return on Investment (ROI) for retail sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. The retail sector was selected because it plays a significant role in the national economy and is one of the sectors most affected by changes in consumer behavior. The research method employed a quantitative approach using purposive sampling, yielding 114 observation samples. The results of the study indicate that, individually, the Current Ratio, Inventory Turnover, and Sales Growth do not have a significant effect on Return on Investment, whereas Return on Equity and the Debt to Asset Ratio have a significant effect on Return on Investment. Simultaneously, all independent variables namely Current Ratio, Return on Equity, Debt to Asset Ratio, Inventory Turnover, and Sales Growth have a significant effect on Return on Investment. These findings indicate that profitability and financing structure play a crucial role in determining the rate of return on investment for companies in the retail sector in Indonesia.